Fantasy Girls: Gender in the New Universe of Science Fiction and Fantasy Television - Helford, Elyce Rae (Rowman & Littlefield Publishers, 2000)
A new collection on women in American television in the 90s uncovers a cultural obsession with tough yet sexy heroines in mythical pasts, the 'girl power' present, and utopic futures. Xena, Buffy, Sabrina, and a host of other characters have become household words, as well as icons of pop culture 'feminism.' Their popularity makes for successful programming, however, how much does this trend truly represent a contemporary feminist breakthrough? And what does it mean for feminism in the next few decades? Fantasy Girls: Navigating the New Universe of Science Fiction and Fantasy Television seeks to explore as well as challenge the power and the promises of this recent media phenomenon. Such TV programming offers the exciting opportunity to rethink established gender norms, but how far is it really pushing the limits of the status quo? Amidst the exuberant optimism of fanzines and doting fan websites, the contributors to this volume endeavor to provide us with a much needed critical analysis of this contemporary trend. These essays explore the contradictions and limitations inherent in the genre, forcing readers to take a fresh and critical look through a variety of lenses including girl power, postfeminism, cyborg feminism, disability politics, queer studies, and much more. Programs covered are Babylon 5, Buffy the Vampire Slayer, Disney's Cinderella, Lois and Clark, Mystery Science Theater 3000, Sabrina the Teenage Witch, Star Trek: Voyager, The X-Files, Third Rock from the Sun, and Xena: Warrior Princess.